Tooth Autotransplantation. A Review - P. Černochová (Czech Dental Chamber, 2009)
Objective: The present articles reviewed literature deals with tooth autotransplantation as far as the successfulness is concerned. Material and methods: The authors searched internet databases (Medline, EBM, Embase, Web of Science, Lilacs) with the assistance of a professional librarian. The search was supplemented with the author's in the PubMed database in the lists of used literature of the available full texts of papers dealing with the evaluation of successfulness of tooth autotransplantation. The detailed analysis selected articles fulfilling entry criteria - tooth autotransplantation in human subjects, well described methodology and evaluation, precisely defined successfulness criteria, minium duration of the observation for one year. Results: The search process made it possible to identify 279 articles dealing with tooth autotransplantation in the title or abstract, which enabled to obtain 76 full tests dealing with their successfulness. The entry criteria for selection into a detailed analysis were fulfilled by 23 articles. The survival of transplants was in the range of 72 to 100% and the success ratio was from 37 to 97.5%. The success rate was influenced by the type of the donor tooth, developmental state of the transplant, damage to the periodontium ligament and subsequent orthodontic movement. Inflammatory resorption was detected in 0 to 35% and ankylosis occurred in 0 to 33.3 % of the cases. Conclusion: It has been demonstrated that tooth autotransplantation is a successful and clinically suitable method especially in certain indication.